Black girls and referrals: racial and gender disparities in self-reported referral to substance use disorder assessment among justice-involved children - Micah E. Johnson; Shawnta L. Lloyd; Skye C. Bristol; Amy L. Elliott; Linda B. Cottler (BMC, 2022)
Abstract Background There is a higher prevalence of substance use disorder (SUD) among justice-involved children (JIC). It is critical to ensure that JIC who report current use are referred for SUD assessment and potentially life-saving treatment services. Prior research suggests that certain minoritized groups may be less likely to have ever been referred for screening, and research on intersectionality suggests that these disparities may be exacerbated for racially minoritized females. Methods Multivariate logistic regression and interaction effects were employed to analyze longitudinal data from the Florida Department of Juvenile Justice on 12,128 JIC who reported SU in the past 6 months. The main and interaction effects of race and gender on the odds of having a history of reporting a referral to SUD assessment were tested. The primary outcome variable was a self-reported measure of a youth's history of being referred to service. The control variables included substance type, household income, current SU problems, history of mental health problems, number of misdemeanors, risk to recidivate, and age at first offense. Results There were no significant differences in the likelihood of having a history of reporting being referred to SUD assessment between White females, White males, and Latinx females. However, Black females (AOR = 0.62), Latinx males (AOR = 0.71), and Black males (AOR = 0.65) were significantly less likely to self-report having a history of being referred than White males. Black females were 34% likely to report a history of being referred as White males and females. Conclusion In this sample, Black females who use substances were substantially less likely to self-report being referred to SUD screening. According to officials, FLDJJ has solid process to ensure referrals are made. Therefore, the results are likely to be due to external factors and alternative explanations. Community leaders and stakeholders may consider culturally relevant and gender-sensitive programs to expand access to services for minoritized adolescents in their communities, schools, and other institutions.